2007
DOI: 10.1007/s00425-007-0614-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rice tryptophan decarboxylases and their direct involvement in serotonin biosynthesis in transgenic rice

Abstract: L-Tryptophan decarboxylase (TDC) and L-tyrosine decarboxylase (TYDC) belong to a family of aromatic L-amino acid decarboxylases and catalyze the conversion of tryptophan and tyrosine into tryptamine and tyramine, respectively. The rice genome has been shown to contain seven TDC or TYDC-like genes. Three of these genes for which cDNA clones were available were characterized to assign their functions using heterologous expression in Escherichia coli and rice (Oryza sativa cv. Dongjin). The purified products of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
180
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(187 citation statements)
references
References 37 publications
4
180
3
Order By: Relevance
“…In transgenic rice (Oryza sativa L.) that lack the downstream enzyme serotonin N-acetyltransferase (SNAT), which is involved in the conversion of serotonin to melatonin, serotonin content was increased and was associated with increased coleoptile growth but slower overall seedling growth [37] . In comparison, an earlier study by Kang et al (2007) found that overexpression of TDC, which despite increasing serotonin levels by up to 25 fold, showed no difference in growth. This suggests that it is not purely carbon flux through the pathway, which is important but overall levels of each of the metabolites in the pathway [38] .…”
Section: Vegetative Growth and Morphogenesiscontrasting
confidence: 62%
See 1 more Smart Citation
“…In transgenic rice (Oryza sativa L.) that lack the downstream enzyme serotonin N-acetyltransferase (SNAT), which is involved in the conversion of serotonin to melatonin, serotonin content was increased and was associated with increased coleoptile growth but slower overall seedling growth [37] . In comparison, an earlier study by Kang et al (2007) found that overexpression of TDC, which despite increasing serotonin levels by up to 25 fold, showed no difference in growth. This suggests that it is not purely carbon flux through the pathway, which is important but overall levels of each of the metabolites in the pathway [38] .…”
Section: Vegetative Growth and Morphogenesiscontrasting
confidence: 62%
“…In comparison, an earlier study by Kang et al (2007) found that overexpression of TDC, which despite increasing serotonin levels by up to 25 fold, showed no difference in growth. This suggests that it is not purely carbon flux through the pathway, which is important but overall levels of each of the metabolites in the pathway [38] .…”
Section: Vegetative Growth and Morphogenesiscontrasting
confidence: 62%
“…In accordance with this, the simultaneous overexpression of a gene encoding a functional TDC and OASA1D resulted in the accumulation of serotonin at a high concentration (Dubouzet et al unpublished results). Kang et al (2007) similarly reported the accumulation of serotonin in the rice seedlings that express a TDC gene under the control of maize ubiquitin promoter.…”
Section: Defensive Role Of Trp Pathway-derived Secondary Metabolismmentioning
confidence: 95%
“…This hypothesis is consistent with results showing that TDC overexpression in rice does not result in a massive increase of tryptamine, in contrast to the huge increase of tyramine in tyrosine decarboxylase (TYDC) overexpression. 10 The small increase of tryptamine or/and serotonin in transgenic rice plants, despite the overexpression of TDC, has been ascribed to the absence of an increased tryptophan level. Therefore, serotonin synthesis seems to be regulated by two rate-limiting steps: tryptophan level and the induction of TDC in plants.…”
Section: Regulation Between Tryptophan and Serotonin Biosynthesismentioning
confidence: 99%